ANALYSIS OF THE EFFICIENCY LEVEL OF SHARIA RURAL FINANCING BANK (SRFB ) USING DATA ENVELOPMENT ANALYSIS (DEA) - Mariana, Leyla; Harun, Harun (Muhammadiyah University Press, 2020)
This research aims to analyze the efficiency level of Sharia Rural Financing Bank (SRFB) in Surakarta. This study used data from four Rural Sharia Banks taken from www.ojk.co.id, which published its annual report. This study conducted input-output variables with the Data Envelopment Analysis (DEA) method as a tool of analysis. The results of the research showed that the SRFB Dana Amanah is indicated as efficient during the 2017 period. The other three are indicated as inefficient in the last quarter. The inefficiency source came from its operational cost and its incapability to get higher output.